Dinamika Hubungan Antarumat Beragama: Pola Hubungan Muslim dan Hindu di Bali - Fahham, Achmad Muchaddam (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2018)
In 2015, in terms of religious harmony in Indonesia, Bali Province was ranked second. The province of Bali received a score of 81.6 percent and was under the province of NTT which obtained a value of 83.3 percent. The acquisition of the harmony index shows that generally the relationship between religious believers in Bali is harmonious. Nevertheless, this does not mean that Bali is protected from the problems of relations between religious believers. This study aims to explain the pattern of relations between Islamic and Hindu communities in Bali. This study uses a qualitative approach, the data is collected through literature studies and interviews with several informants who are selected purposively. The findings obtained show that the pattern of relations between Muslim and Hindu followers is not single, but diverse. There are associative patterns and there are also patterns of disassociative relationships. Associative relationships are divided into three, namely cooperation, accommodating, and tolerance, while associative relationships are divided into two, namely competitive and conflict. Factors that encourage the birth of associative relationships are historical factors, economic interests, and integration factors. On the other side, the determinants of the birth of a disassociative relationship are factors of economic jealousy, lack of understanding of the teachings of Islam, communication and the strong customs implemented in Bali.Di tahun 2015, dalam hal kerukunan umat beragama di Indonesia, Provinsi Bali menempati peringkat kedua. Provinsi Bali memeroleh nilai 81,6 persen dan berada di bawah Provinsi NTT yang memeroleh nilai 83,3 persen. Perolehan indeks kerukunan tersebut menunjukkan secara umum hubungan antarumat beragama di Bali adalah harmonis. Meskipun demikian, ini bukan berarti Bali terhindar dari problema hubungan antarumat beragama. Studi ini bertujuan untuk menjelaskan pola hubungan antarumat Islam dan Hindu di Bali. Studi ini menggunakan pendekatan kualitatif, data-datanya dikumpulkan melalui studi pustaka dan wawancara dengan beberapa informan yang dipilih secara purposive. Temuan yang diperoleh menunjukkan bahwa pola hubungan antarumat Islam dan Hindu tidak tunggal, tetapi beragam. Ada pola hubungan yang asosiatif dan ada pula pola hubungan yang disasosiatif. Hubungan yang asosiatif dipilah menjadi tiga yakni kerja sama, akomodatif, dan toleransi, sementara hubungan yang diasosiatif dibagi menjadi dua, yakni kompetitif dan konflik. Faktor yang mendorong lahirnya hubungan yang asosiatif adalah faktor historis, kepentingan ekonomi, dan faktor integrasi. Sementara faktor penentu lahirnya hubungan yang disasosiatif adalah faktor kecemburuan ekonomi, ketidakemengertian terhadap ajaran agama Islam, komunikasi dan kuatnya adat yang berlaku di Bali.